Pengaruh Pemberdayaan Sikap Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Padang Lawas - Jhon Arief; Annisafitri annisafitri; Reza Affandi; Ahadiluly Ambiar (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
Problem of this study is how influence of empowerment on employee’s performance. How influence of work attitude on employee’s performance. How influence work environment on employee’s performance. How influence of empowerment, work attitude and work environment on employee’s performance. The purpose of this study to determine and analyze the effect of empowerment on employee’s performance. Determine and analyze the effect of work attitude on employee’s performance. Determine and analyze the effect of work environment on employee’s performance. Determine and analyze the effect of empowerment, work attitude and work environment on employee’s performance. Sample in the study is 36 employee’s. Data analysis techniques used in this study is descriptive analyze and multiple linear regression analysis. The results of the study indicate empowerment variable has a positive and significant effect on employee’s performance. Work attitude variable has a positive and significant effect on employee’s performance. Work environment variable has a positive and significant effect on employee’s performance. Empowerment, work attitude and work environment variable’s has a positive and significant effect on employee’s performance.